The new social learning : connect. collaborate. work. - Bingham, Tony; Conner, Marcia L., 1965- (ATD Press, 2015)
In this newly revised and updated edition, the authors dispel organizational myths and fears about social media. By sharing the success stories of socially engaged companies and people, this book persuasively makes the case for using social media to encourage knowledge transfer and real-time learning in a connected and engaging way. New case studies about innovative organizations such as Boston Children's Hospital, National Australian Bank, LAZ Parking, Sanofi Pasteur, Cigna, CENTURY 21, and Roche Pharmaceuticals illustrate cutting-edge social learning approaches that cultivate environments where great people can do their best work. It lays the foundation for improving the way you engage with colleagues, collaborate with teams anywhere in the world, and build workforce capability. --